Linking nutritional support with treatment of people living with HIV: Lessons being learned in Kenya - Bryan, Elizabeth; Gillespie, Stuart; Nangami, Mabel (International Food Policy Research Institute, 2008)
While clinical care providers, program managers and other stakeholders increasingly recognize the critical importance of nutrition for the treatment of HIV and AIDS, interventions that link nutritional support to treatment are relatively new. The Academic Model for Prevention and Treatment of HIV/AIDS (AMPATH) initiated one such intervention in 2002 in western Kenya with a large scale-expansion currently underway with the support of World Food Programme commodity donations, and fresh foods grown on AMPATH production farms.